1999
DOI: 10.1182/blood.v94.12.4122.424k35_4122_4131
|View full text |Cite
|
Sign up to set email alerts
|

Hypofibrinogenemia Associated With a Heterozygous Missense Mutation γ153Cys to Arg (Matsumoto IV): In Vitro Expression Demonstrates Defective Secretion of the Variant Fibrinogen

Abstract: We genetically analyzed a case of hypofibrinogenemia that showed no bleeding or thrombotic tendency. Direct sequencing of a polymerase chain reaction-amplified γ-chain gene segment showed a novel nucleotide substitution. This heterozygous mutation encodes both Cys (TGT) and Arg (CGT) at residue 153. To examine the basis for the fibrinogen deficiency, we prepared expression vectors containing mutant γ-chain DNAs encoding γ153R and γ153A for in vitro expression in Chinese hamster ovary (CHO) cells. Enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 27 publications
2
46
1
1
Order By: Relevance
“…The Matsumoto IV (γ153 Cys→Arg) mutation affects the proximal A region of the γD domain. 17 Transient expression of 153 Arg γ chains with Aα and Bβ chains in Chinese hamster ovary cells demonstrated that, although the variant chain was synthesized, no variant fibrinogen molecules were secreted into the culture medium.…”
Section: Mutations Affecting Intracellular Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The Matsumoto IV (γ153 Cys→Arg) mutation affects the proximal A region of the γD domain. 17 Transient expression of 153 Arg γ chains with Aα and Bβ chains in Chinese hamster ovary cells demonstrated that, although the variant chain was synthesized, no variant fibrinogen molecules were secreted into the culture medium.…”
Section: Mutations Affecting Intracellular Assemblymentioning
confidence: 99%
“…Since γ153 Cys forms an inter chain S-S bond to γ182 Cys it appears that either, γ153 Cys has a direct role in complex formation or, that the freed thiol at γ182 impairs the formation of S-S bonds in the αγ or βγ complexes. 17 The Bβ353 Leu→Arg and Bβ400 Gly→Asp mutations 18 are located in the distal P region of the βD domain. 11 Heterozygosity for either lowers fibrinogen levels by approximately 50%, whereas homozygosity produces afibrinogenemia.…”
Section: Mutations Affecting Intracellular Assemblymentioning
confidence: 99%
“…One of these differences, γ 796 T → A, has been identified previously 10 and has recently been redescribed. 11 In that study, a total of five variations were noted, all of which were identified in our study. In agreement with our interpretation, these variations were classified by the authors as errors in the Genbank entry.…”
Section: Resultsmentioning
confidence: 71%
“…Culture media and cell lysates were prepared, and fibrinogen concentrations were measured by ELISA. 15…”
Section: Immunoblotting Analysis and Enzyme-linked Immunosorbent Asmentioning
confidence: 99%